Biological nitrogen fixation detected under Antarctic sea ice - Shiozaki, Takuhei; Fujiwara, Amane; Inomura, Keisuke; Hirose, Yuu; Hashihama, Fuminori; Harada, Naomi (Nature geoscience, 2020)
Nitrogen fixation is the primary source of reactive nitrogen in the ocean. Most ecological models do not predict nitrogen fixation in the Antarctic Ocean because of the low availability of iron and high abundance of nitrogen. Here we extensively examined nitrogen fixation in the Antarctic Ocean, and found substantial nitrogen fixation (maximum: 44.4 nmol N l −1 d −1 ) near the Antarctic coast, especially around ice-covered regions. The nitrogenase gene ( nifH ) was detected at all coastal stations, including stations where no nitrogen fixation was found. At the stations where nitrogen fixation was detected, the nitrogen-fixing cyanobacterium UCYN-A (Candidatus ‘ Atelocyanobacterium thalassa ’) dominated nifH gene expression, and the nifH sequence was identical to that of the major oligotype in tropical and subtropical oceans. Our results suggest that marine nitrogen fixation is a ubiquitous process in the global ocean, and that UCYN-A is the keystone species for making it possible. Observational evidence of cyanobacterial activity in the Antarctic Ocean suggests that nitrogen fixation could be a ubiquitous process in the global ocean.